Characteristics and Associated Survival of Patients Diagnosed With Non–Small Cell Lung Cancer in a Designated Lung Cancer Program in Western Kenya - Naftali Busakhala; Lawrence Atundo; Hillary Kiprono; Kibet Keitany; Elias Melly; Ruth Ruto; Madrine Wanja; Daniel Chepsiror; Hussain Rangoonwala; Cornelius Kipchirchir; Erick Chesori; John Oguda; et al. (JCO Global Oncology)
PURPOSEAlthough lung cancer is a major cause of cancer incidence and mortality worldwide, lung cancer studies in sub-Saharan Africa are scarce. Here, we present outputs from a designated lung cancer program in western Kenya, part of the Multi-National Lung Cancer Control Program, which focused on case finding, diagnosis, and treatment.METHODSWe retrospectively reviewed patients with pathologically confirmed non–small cell lung cancer (NSCLC) enrolled in this program at Moi Teaching and Referral Hospital from January 2018 to December 2022. Clinical data were analyzed using descriptive statistics, Kaplan-Meier methods, and proportional hazards regression model.RESULTSTwo hundred forty-nine patients diagnosed with NSCLC were included with a median age at diagnosis of 61 (IQR, 52-70) years. Most patients were married (n = 177; 71%) and nonsmokers (n = 177; 71%) with 58 (23%) having received tuberculosis treatment and 93 (37%) having Eastern Cooperative Oncology Group (ECOG) performance status (PS) of [Formula: see text]2. At diagnosis, adenocarcinoma was the prominent histology (n = 187; 75%) along with clinical stage IV (n = 195; 78% stage IV) or unstaged (n = 40; 16%) disease. Most patients received chemotherapy and radiotherapy (n = 176; 71%) with few palliative care referrals (n = 2; 0.8%). The median overall survival (OS) was only 3.7 months (IQR, 2.7-5.4). ECOG PS (3 or 4) and being unstaged were predictors of poor 1-year OS.CONCLUSIONPatients with NSCLC enrolled in this program presented with advanced disease and poor survival. Despite a designated case finding effort, late diagnosis remained common and highlights a need for locally relevant interventions targeting community and provider education as well as innovative diagnostics that can improve early recognition of lung cancer. These interventions must also be paired with access to proven treatments including molecular therapies and palliative care which can extend lung cancer survival.